Optimal irrigation at various soil types for soybean production. Issue 1 (February 2021) - Suriadi, A; Zulhaedar, F; Nazam, M; Hipi, A
Abstract: Water distribution officials at the secondary level mostly have not considered type of soil to distribute water irrigation for soybean cultivation. This study aimed to determine the optimal irrigation for soybean production at various soil types in Lombok. The study was conducted in 3 texture soil types of sandy loam, loam and clay. Each soil type was applied four treatments of irrigation water: 1 time (15 days after sowing, DAS); 2 times (15 and 45 DAS); 3 times (15, 30 and 45 DAS) and 4 times (15, 30, 45 and 60 DAS) and arranged in a completely randomized block design and repeated five times. The results showed that the highest soybean yield was obtained 4 times irrigation in sandy loam soil. In loam soil type, the highest yield of soybean was obtained at 4 times although this was not significantly different with 3 times irrigation. In clay soil type, the highest soybean yield was obtained at 4 times irrigation treatment, but this was almost a similar yield with 3 times irrigation treatments. The study suggests that schedule water delivery for soybean cultivation is recommended to increase soybean production in irrigated land.